Analysis of postoperative radiotherapy for non-metastatic head and neck adenoid cystic carcinoma based on SEER data. Issue 8 (August 2022) - Du, Yan; Zeng, Yong
Objective: The postoperative role of adjuvant radiotherapy in non-metastatic head and neck adenoid cystic carcinoma (ACC) remains controversial. We analyzed adjuvant radiotherapy's effect on surgical patient survival. Methods: Patients diagnosed with ACC from 2004 to 2015 in the Surveillance, Epidemiology, and End Results database were analyzed. The overall survival (OS) and disease-specific survival (DSS) of patients after adjuvant radiotherapy were assessed using the Kaplan–Meier and multivariate Cox methods. Propensity score matching (PSM) was performed to adjust confounders between patients with or without adjuvant radiotherapy; a forest plot was generated by subgroup analysis. Results: The study included 742 patients. In the PSM cohort, adjuvant radiotherapy did not improve OS or DSS. Radiotherapy was not a protective factor for OS or DSS in the univariate and multivariate Cox proportional hazard models. In the subgroup analysis, postoperative radiotherapy improved the OS of female and N1-stage patients and those with oropharyngeal tumors or over 79 years and the DSS of N1-stage patients. Conclusions: Postoperative radiotherapy showed different benefits in ACC patients, and postoperative radiotherapy recommendations should be individualized. Female and N1-stage ACC patients and those with oropharyngeal tumors or patients over 79 years without distant metastases postoperatively could benefit from adjuvant radiotherapy.